Growth, Yield, and Sugar Content of Different Varieties of Sweet Corn and Harvest Time - St. Subaedah; Edy Edy; Kiky Mariana (International Journal of Agronomy)
The demand for sweet corn has increased largely because of its superior tastes compared with common corn. This research was conducted to analyze the growth and yield and sugar content of sweet corn seed on different varieties and harvest times. This research was conducted in South Sulawesi, Indonesia, from April to August 2018. The research was designed under a split-plot design. The main plot consisted of planting systems (single row and twin-row), whereas subplots consisted of three varieties (Bonanza, Talenta, and Master Sweet) and three harvest times (65, 70, and 75 days after planting). Variables measured consisted of plant height, cob length, cob weight, estimation of cob weight per hectare, and sugar content. Significant varietal differences were observed in plant height, cob length, cob weight, and sugar content. Master Sweet variety had the greatest plant height and cob length, whereas Bonanza variety produced the greatest cob weight, cob weight per hectare, and sugar content. Harvest time at 75 days after planting (DAP) produced the greatest plant height in the twin-row system, cob diameter, cob weight, and cob weight per hectare, whereas that at 65 DAP had the greatest plant height in control and sugar content. The twin-row system produced the greatest cob weight per hectare (22.33 ton/ha). This study recommends the use of Bonanza variety and harvest at 65 DAP to produce the greatest sweet corn cob per hectare.